(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of this research is to determine the scope of contempt of court in Indonesia, to find models of criminal law policies that can be used to prevent and overcome acts of contempt of court in Indonesia, and to analyze the implementation of contempt of court in court decisions in Indonesia. The research is a normative juridical study that places Law as a system of norms. Library material becomes secondary data from primary, secondary, and tertiary legal materials. At the same time, the approach uses a comparative and case method. The results showed that the coverage of contempt of court is all actions in the form of threats, obstacles, disturbances, and challenges to the ongoing judicial process, resulting in a fair trial process being difficult to obtain, which occurs inside or outside the trial. These acts can occur in all sub-judicial systems, with various subjects of offense starting from court visitors, witnesses, defendants, advocates, the press, and even the apparatus itself. Generally, contempt of court in Indonesia occurs both at trial and outside of court. The form is criminal and civil contempt, which consists of scandalizing, misbehaving, obstruction, and obeying the court and sub-judice rule. The criminal law policies that are carried out against contempt of court with formulation policies (making their own rules and classifications of actions and formulations of sanctions that are adjusted to the quality of the act) regulatory model by placing it in a separate chapter in the Criminal Code.